Effect of Age at Menopause on Disease Presentation in Early Rheumatoid Arthritis: Results From the Canadian Early Arthritis Cohort. Issue 5 (May 2015) - Wong, Lauren E.; Huang, Wei‐Ti; Pope, Janet E.; Haraoui, Boulos; Boire, Gilles; Thorne, J. Carter; Hitchon, Carol A.; Tin, Diane; Keystone, Edward C.; Bykerk, Vivian P.; for the Canadian Early Arthritis Cohort Investigators
<x xml:space="preserve">Abstract</x> Objective Studies suggest that hormonal states affect disease characteristics in women with rheumatoid arthritis (RA). This study investigated how age at menopause affects disease in women presenting with early RA. Methods This was a cross‐sectional study of postmenopausal women with early RA under age 65 years at time of enrollment in the Canadian Early Arthritis Cohort. RA‐related disease characteristics in women who had early age at menopause (EM; age at menopause <45 years) were compared to those who had usual age at menopause (age at menopause ≥45 years). The t‐test was applied to continuous variables and the chi‐square test to categorical variables. Multivariate logistic regression analysis was used to adjust for age at menopause, smoking, and use of exogenous hormones. Results A total of 534 women were included; 93 were in the EM group. The age at RA onset was similar between groups. The EM group had higher mean patient global and pain scores and was more likely to be rheumatoid factor (RF) positive and meet the 1987 American College of Rheumatology criteria for RA. Using multivariate logistic regression, the EM group was more likely to be RF positive (odds ratio 2.2 [95% confidence interval 1.3–3.8], P = 0.005). Symptom duration, joint counts, Disease Activity Score in 28 joints, Health Assessment Questionnaire scores, and inflammatory markers did not differ between groups. Conclusion These data suggest that early age at menopause, compared to usual age at menopause, is associated with seropositivity in women with early RA.